PREPARASI MAGNETIT PASIR BESI TERDISPERSI NATRIUM SITRAT UNTUK ADSORPSI Au(III) - Ricka Prasdiantika; Susanto Susanto (Neo Teknika, 2017)
This study aims to the preparation material magnetite (Fe3O4) of iron sand dispersed sodium citrate (Fe3O4 @citrate), and its application to adsorption of metal ions Au(III). Preparation was done by was separating the magnetic material of iron sand using an external magnet and washed with H2O. Magnetite was soaked with sodium citrate solution 0.5 M as the dispersion medium. Materials were characterized by Fourier Transform Infrared (FT-IR) Spectrophotometer, and Transmission Electron Microscope (TEM). Adsorption ability of the material to Au(III) was evaluated in HAuCl4 solution with a concentration of Au(III) 200 ppm and pH 3 for 120 minutes. Concentration of Au(III) which was not adsorbed was analyzed with Atomic Absorption Spectroscopy (AAS). The characterization results indicate that Fe3O4@citrate successfully prepared by having a better particle dispersion and aggregate less than Fe3O4 iron sand without citrate. Material Fe3O4@citrate tested the ability of metal ion adsorption on Au(III) at 200 ppm HAuCl4 solution with a pH of 3. Material Fe3O4@citrate which was able to adsorb metal ions Au(III) with the amount of 83.667 ± 0.727 mg/g.Keywords: Magnetite Iron Sand, Particle Dispersion, Solution Sodium Citrate, Adsorption Au (III)